PENGEMBANGAN BUKU CERITA BERSERI UNTUK SISWA KELAS V SDN 14 PONTIANAK SELATAN - Natasya, Dya; Salimi, Asmayani; Ghasya, Dyoty Auliya Vilda (Universitas Tanjungpura, 2025)
The lack of motivation and enthusiasm for learning in class V students at SD Negeri 14 Pontianak Selatan is one of the backgrounds for developing this series of storybooks as an effort to increase their learning motivation. This research aims to produce a series of storybooks